2017
DOI: 10.1128/genomea.00844-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Escherichia coli ABWA45, an rmtB -Encoding Wastewater Isolate

Abstract: We present the complete genome sequence of Escherichia coli ABWA45, a 16S rRNA methyltransferase-producing wastewater isolate. Assembly and annotation resulted in a 5,094,639-bp circular chromosome and four closed plasmids of 145,220 bp, 113,793 bp, 57,232 bp, and 47,900 bp in size. Furthermore, a small open plasmid (7,537 bp in size) was assembled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Beyond their intrinsic resistance genes, recent data also suggests that naturalized wastewater E. coli may be permissive and competent at acquiring antibiotic resistance genes from clinical strains. For example, an E. coli isolate collected from a hospital wastewater system in Switzerland by Zurfluh et al (2017a , b) , which was subsequently shown to be a naturalized wastewater strain by Zhi et al (2019) , possessed various carbapenem resistance genes, including a plasmid-encoded 16S rRNA methyltransferase gene ( rmtB ) and the β-lactamase bla TEM-1b —common constituents in extended spectrum β-lactamase (ESBL) clinical isolates of E. coli . Interestingly, naturalized wastewater strains collected in other studies lacked these particular genes ( Zhi et al, 2019 ); however, strains from Zhi et al (2019) were isolated from municipal sewage, whereas Zurfluh et al (2017b) isolated their naturalized E. coli strain directly from a hospital sewage/wastewater system.…”
Section: Naturalized Wastewater Microbes and The Co-evolution Of Anti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond their intrinsic resistance genes, recent data also suggests that naturalized wastewater E. coli may be permissive and competent at acquiring antibiotic resistance genes from clinical strains. For example, an E. coli isolate collected from a hospital wastewater system in Switzerland by Zurfluh et al (2017a , b) , which was subsequently shown to be a naturalized wastewater strain by Zhi et al (2019) , possessed various carbapenem resistance genes, including a plasmid-encoded 16S rRNA methyltransferase gene ( rmtB ) and the β-lactamase bla TEM-1b —common constituents in extended spectrum β-lactamase (ESBL) clinical isolates of E. coli . Interestingly, naturalized wastewater strains collected in other studies lacked these particular genes ( Zhi et al, 2019 ); however, strains from Zhi et al (2019) were isolated from municipal sewage, whereas Zurfluh et al (2017b) isolated their naturalized E. coli strain directly from a hospital sewage/wastewater system.…”
Section: Naturalized Wastewater Microbes and The Co-evolution Of Anti...mentioning
confidence: 99%
“…For example, an E. coli isolate collected from a hospital wastewater system in Switzerland by Zurfluh et al (2017a , b) , which was subsequently shown to be a naturalized wastewater strain by Zhi et al (2019) , possessed various carbapenem resistance genes, including a plasmid-encoded 16S rRNA methyltransferase gene ( rmtB ) and the β-lactamase bla TEM-1b —common constituents in extended spectrum β-lactamase (ESBL) clinical isolates of E. coli . Interestingly, naturalized wastewater strains collected in other studies lacked these particular genes ( Zhi et al, 2019 ); however, strains from Zhi et al (2019) were isolated from municipal sewage, whereas Zurfluh et al (2017b) isolated their naturalized E. coli strain directly from a hospital sewage/wastewater system. Considering that antibiotic residues in untreated hospital wastewater are much greater than those typically seen in municipal wastewater ( Karthikeyan and Meyer, 2006 ), heightened exposure to antibiotics in hospital wastewater may provide the necessary selective pressure for the retention of some AR genes (i.e., carbapenem resistance genes and beta-lactams) in naturalized wastewater E. coli strains ( Zurfluh et al, 2017b ).…”
Section: Naturalized Wastewater Microbes and The Co-evolution Of Anti...mentioning
confidence: 99%
See 1 more Smart Citation